LA RESPONSABILIDAD DE LOS ADMINISTRADORES. - JOSE MIGUEL ZURITA VICIOSO (Revista Internacional de Doctrina y Jurisprudencia, 2015)
Directors of corporations must act in the exercise of their company functions, fulfilling the duties that are required by law because, otherwise, their personal assets may be exposed to compensation for the damages they have caused to the society they are representing, its partners or third parties. It is therefore important to know what actions can be urged against the Directors and the causes they may claim to be exempted.